Tinjauan Manajemen Proyek Dalam Penentuan Skala Prioritas Pembangunan Jalan Di Kabupaten Kaur - Yunita Mauliana (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2023)
Regency roads are local roads which do not include roads connecting the district capital to other districts, but their network is diverse as a link for local activities, namely connector roads between villages, between sub-districts, production center roads and environmental roads in residential areas. This research focuses on roads in Kaur Selatan District and Maje District, Kaur Regency, Bengkulu Province with a total length of 128.50 km with a total of 68 sections. There are several sub-district roads which are a road network that is integrated with national roads. In general, this road section is often used by various types of vehicles, from light to heavy vehicles. Utilization of roads that do not match their class and the influence of the weather climate in areas that are quite extreme result in landslides so that the road body becomes narrow and heavily damaged. As a result of damage to existing roads, community activities are hampered. The purpose of this research is to provide information to the Bengkulu Regency government in preparing priority planning, determining the type of pavement that is appropriate to the location of the road section and determining the calculation of the costs required. The results of research and calculations show that the cost required for road repairs is IDR. 70,788,844,000 for a period of 5 years. The priority scale consists of 17 sections with a cost of Rp. 57,541,204,000.